Etos Kerja dan Korelasinya dengan Peluang dan Tantangan Profesionalitas Masyarakat Muslim di Era Modern - Mohammad Irham (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2012)
Based on writer observation, there are few works on work ethic. There is no sole theory could explains all phenomena and how to make weak to become stronger and better. Sometimes work ethic influenced by belief, like a religion. Sometimes it is affected by economic growth in a community. As a complex religion, Islam explains about work ethic in adequate manner. At least, this could be understood through worship concept that poses unlimited meanings, which work ethic is included in.